Ethanol Sensing with Pure and Boric Acid Doped Eectrospun CuInS2 Nanofibers in the Presence of Relative Humidity - Yağcı, Özlem; Ömür, Birsel Can; Altındal, Ahmet; SARIER, NİHAL; ARAT, REFİK (ELSEVIER SCI LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND, 2019)
The influence of boric acid doping on ethanol vapor sensing performance of electrospun copper indium disulfide (CuInS2) nanofibers in the presence of various levels of relative humidity was examined for the first time. Pure and boric doped CuInS2 nanofibers are prepared through electrospinning method and characterized by X-ray diffraction, scanning electron microscope, Fourier transform infrared spectroscopy and Thermogravimetric analysis techniques. It was found that not only the ethanol sensing performance but also base line current of the CuInS2 nanofiber based sensors are greatly influenced by the boric acid doping level. Maximum sensitivity was obtained with pure CuInS2 under humid conditions. Kinetic studies indicated that ethanol vapor adsorption kinetics strongly depend on level of the relative humidity and the ethanol concentration.
Keywords: Thin-Films; Gas Sensors; Conter-Electrode; Elovich Equation; Fabriaciton; SNO2; Nanocrystals; Kınetics; Performance; Sorption